THE REBELLION BEHAVIOR OF CARRIE WHITE’S CHARACTER IN CARRIE MOVIE (2013) - Lifu, Atika Rosita Lifu; Natsir, Muhammad; Valiantien, Nita Maya (Fakultas Ilmu Budaya Universitas Mulawarman, 2022)
The purposes of this research are to found out about the rebellion behavior of Carrie White’s character and how it portrayed through her characterization and also to found out about the resolution of her rebellion behavior in Carrie movie (2013). The design of this research was qualitative research. The data in this research were from the dialogue, action, scene, and script of the movie which is Carrie movie (2013). The data were analyzed using the rebellion theory by Arnett and the characterization theory by Kenan. This research has three research questions, the first one is what is the rebellion behavior of Carrie White’s character portrayed in the movie based on Arnett’s adolescent theory?, the second one is how is Carrie White’s rebellion behavior portrayed in the movie through the characterization theory by Rimmon Kenan?, and the last one is what are the resolutions of Carrie White’s rebellion behavior portrayed in the movie?. The result showed that Carrie White has three kinds of rebellion behavior according to the first research question based on Arnetts theory which is the conflict with parents, mood disruption, and risk behavior, and also the second research question that Carrie White characterization was portrayed through Kenan’s theory which is the indirect definition. The resolution of this research is that Carrie White at the end of the movie felt sorry that she had rebelled against her mom.